Integration of Local Wisdom with Environmental Law - Matnuril; Murthir Jeddawi; Kusworo; Bambang Supriyadi (International Journal of Science and Society, 2019)
This study aims to identify the values ​​of local wisdom with an insight into environmental law owned by the people of Nagari Pariangan. This research uses a qualitative approach with descriptive methods. Research data collection using observational methods, focus group discussions, interviews, and documentation. The results showed that the values ​​of local wisdom of Nagari Pariangan as a guide to people's lives in protecting their environment are manifested in customary norms that natural resources in the form of land/fields/ rice fields, forests and rivers cannot belong to individuals but belong to indigenous people/tribes and in its management must obtain approval from Ninik Mamak. The Tigo Tungku Sajarangan government integrates the customary norms of Nagari Pariangan with environmental laws that are realized in consensus agreement between Ninik Mamak in every development plan that is proclaimed by the Nagari Government, Regency, Provincial and Central Governments. If the results of the consensus were unanimous then that would be the final decision carried out by each of the nephews/ community's children.